Goat genetic diversity of India - An overview - N.K.Verma (Journal of Livestock Biodiversity, 2025)
Indian goats include well deined and documented populations designated by breeds and those (lesser known) which are not studied adequately and least documented. The inadequately studied populations or ’lesser known’, goats form a major chunk (65%) of the total goat population. As per the policy of Govt. of India, all the livestock breeds have to be registered and should ind a place in the gazette of India. There are 28 registered goat breeds as on date. Each breed is known for its utility (Meat/Milk/iber). Most of the goats are multipurpose yielding mainly meat in addition to their other speci ic performance e.g. milk. The complete characterization (phenotypic and genetic) of these populations may indicate the distinctness of some or all of these populations. After confirming the distinctness the population can be assigned the breed status and the useful characteristics of the breed can be utilized for upgrading other non-descript populations.